2018
DOI: 10.1111/cea.13301
|View full text |Cite
|
Sign up to set email alerts
|

Combined administration of anti‐IL‐13 and anti‐IL‐17A at individually sub‐therapeutic doses limits asthma‐like symptoms in a mouse model of Th2/Th17 high asthma

Abstract: Background: Recent studies have demonstrated that Th2 responses have the ability to antagonize Th17 responses. In mouse models of allergic asthma, blockade of Th2-effector cytokines results in elaboration of Th17 responses and associated increases in pulmonary neutrophilia. While these can be controlled by simultaneous blockade of Th17associated effector cytokines, clinical trials of anti-IL-17/IL-17RA blocking therapies have demonstrated increased of risk of bacterial and fungal infections. Identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 77 publications
(119 reference statements)
2
11
0
Order By: Relevance
“…Second, increases in regulatory T cell numbers to control hyperinflammation in the context of comorbidity can decrease Th17 cell numbers to preserve host homeostasis [ 54 ]. Third, several studies have clarified that allergen-induced Th2-type cytokines can suppress Th17 responses [ 44 , 55 ], which supports our finding that only relatively late induction of allergic asthma inhibited preexisting Mav-specific Th17 responses and increased the number of CFUs at 5 w.p.i.…”
Section: Discussionsupporting
confidence: 87%
“…Second, increases in regulatory T cell numbers to control hyperinflammation in the context of comorbidity can decrease Th17 cell numbers to preserve host homeostasis [ 54 ]. Third, several studies have clarified that allergen-induced Th2-type cytokines can suppress Th17 responses [ 44 , 55 ], which supports our finding that only relatively late induction of allergic asthma inhibited preexisting Mav-specific Th17 responses and increased the number of CFUs at 5 w.p.i.…”
Section: Discussionsupporting
confidence: 87%
“…We found that absence of IL‐17A/F or neutralization of IL‐17A alone led to attenuation of severity of experimental allergic asthma, either before sensitization or challenge. These findings are in line with the results of other studies using related mouse models [37, 38]. Moreover, we report that the observed reduction in pulmonary eosinophilic inflammation, AHR and goblet cell hyperplasia correlated with reduced conventional DC frequencies both in the lung and lung draining mediastinal LNs of IL‐17A/F KO allergic animals.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this is the first evidence that links availability of IL‐17 in an experimental asthma model to reduced migration of DCs with a possible effect in attenuation of severity of inflammation and AHR. Given that IL‐17 and Th17 cells are involved in asthma development and shown to be associated with severity and course of disease [79, 37, 38], we believe this is an important mechanism by which this cytokine enhances inflammation and associated pathologies such as those in asthma and allergy.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17-producing cells are involved in various inflammatory diseases, such as psoriasis [ 70 , 71 , 72 , 73 , 74 ], asthma [ 75 , 76 , 77 , 78 , 79 ], and atopic dermatitis [ 80 , 81 , 82 ], and contribute to the development of host defense against microorganisms [ 83 , 84 , 85 , 86 ]. As the importance of IL-17-producing cells in the human body, IL-17-targeted biologics treatment is proven by the current advancement of this field.…”
Section: Clinical Sign and Biomarker For Drug Eruptionmentioning
confidence: 99%